The cesium 62P3/2 to 82S1/2 line shape broadened by He, Ar, and Kr. (July 2020) - True, Timothy M.; Rice, Christopher A.; Perram, Glen P.
Highlights: Observed broadening and shift rates for the Cs line shape with He, Ar, and Kr. Observed rates are approximately 4–6 times larger than for the D1 line. A red satellite is observed at 12 cm − 1 for Kr. Abstract: Pump modulated laser absorption spectroscopy was used to measure the cesium 6 2 P 3 / 2 ⟶ 8 2 S 1 / 2 line shape collisionally broadened by He, Ar, and Kr. The 6 2 P 3/2 state was prepared by pumping the D 2 transition while a probe laser was simultaneously tuned across the 8 2 S 1/2 transition. Results were fitted to a summation of Voigt line shapes, simulating the hyperfine splitting, and broadening and shift rates were deduced. The collisional broadening rates, γ, for He, Ar, and Kr are 119 ± 2, 84 ± 12, and 77 ± 7 MHz/Torr and the pressure induced shift rates, δ, are + 31.6 ± 0.2, − 19.6 ± 0.5 and − 17.3 ± 0.5 MHz/Torr respectively. These rates suggest very shallow wells ( < 0.3 cm − 1 ) far out ( > 25Å) in the potential difference curves for Ar and Kr, while the He curve is entirely repulsive. Collision probabilities scale linearly with dipole polarizability. Non-Lorentzian features are readily observed in the far wings at pressures greater than 600 Torr.